2021
DOI: 10.30574/wjarr.2021.9.1.0007
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and anatomical characteristics of Waltheria indica (L.) growing on sandy soils of Binh Thuan province, Vietnam

Abstract: Waltheria indica (L.) is a species in the list of medicinal plants in Vietnam. However, information about this species is still at the basic level. In order to provide more data on this medicinal plant, the present research has gone into further on the characteristics of the plant through morphological classification method, observing the thin slices of vegetative and reproductive organs and measuring with a reticule on the eyepiece and a stage micro-meter equipped for a light microscope. Combination of statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Through the above works, it could be seen that the antibacterial properties of Waltheria indica extracts collected from different regions were different. In this study, the extracts obtained from plants grown in Ham Tien were more resistant than those grown in Tien Thanh; although previous research [7] had shown that plants grown in Ham Tien were smaller and sparser because of their response to low-nutrient and acidic soils. Which mechanism involved was still not well understood.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Through the above works, it could be seen that the antibacterial properties of Waltheria indica extracts collected from different regions were different. In this study, the extracts obtained from plants grown in Ham Tien were more resistant than those grown in Tien Thanh; although previous research [7] had shown that plants grown in Ham Tien were smaller and sparser because of their response to low-nutrient and acidic soils. Which mechanism involved was still not well understood.…”
Section: Discussionmentioning
confidence: 65%
“…There were many studies and reports on botany, phytochemistry, traditional medicinal uses, medicinal properties and toxicity of plants [1,4]. Particularly in Vietnam, in addition to some basic information on morphology, distribution and medicinal uses in books on traditional medicinal herbs [5,6], this plant was studied for its morpho-anatomical characteristics adapted to the drought conditions of Binh Thuan province [7].…”
Section: Introductionmentioning
confidence: 99%